The Effect of Face Masks during COVID-19 Pandemic on Ocular Surface Temperature—A Clinical Thermographic Analysis - Kapelushnik, Noa; Benyosef, Shahar; Skaat, Alon; Abdelkader, Amir; Landau Prat, Daphna; Blum-Meirovitch, Sharon; Leshno, Ari (Diagnostics (Basel), 2022)
Due to the COVID-19 pandemic, the center for disease control and prevention (CDC) recommends face-mask wearing for all people above the age of two years. The wearing of face masks creates a unique airflow towards the ocular surface which may influence the normal physiological conditions of the ocular and periocular surface. Healthy subjects with no ocular history were enrolled in this cross-sectional study. The Therm-App thermal imaging camera was used for ocular surface temperature (OST) measurements during inspirium and expirium. Five regions of interest (ROIs) were used to measure OST: medial conjunctive, cornea, lateral conjunctive, upper eyelid and entire orbital area. Additional measurements in the same locations were made with the upper margin of the mask taped with micropore surgical tape. Thirty-one patients were included in this study. OST during expirium was significantly higher compared to the temperature during inspirium in all locations measured (p < 0.001, paired samples t-test). The temperature of the upper eyelid was higher by more than 0.5 °C during expirium. Taping the mask’s upper edges to the skin resulted in non-significant temperature changes in inspirium vs. expirium. In conclusion, wearing a face mask creates air flow towards the periocular and ocular surface, which changes the OST mostly on the eyelids.